Accuracy of Transabdominal Ultrasonography in Diagnosing Ectopic Pregnancy, Taking SurgicalFindings as Gold Standard - Javed, Muhammad Asif; Niaz, Ayesha; Asim, Uroosa (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the accuracy of transabdominal ultrasonography in diagnosing ectopic pregnancy taking surgical findings as the gold standard.Study Design: Cross-sectional study.Place and Duration of Study: Department of Radiology, Combined Military Hospital, Sialkot from October 2019 to April 2020.Methodology: A total of 211 females with a suspicion of ectopic pregnancy between 18 to 40 years of age were included in this study who fulfilled the selection criteria. Transabdominal sonography was carried out in all patients. The females were then subjected to surgery for confirmation of diagnosis. The findings were noted down on the proforma and were subjected to statistical analysis. Results: The mean age of the patients 28.38±5.61 years, the mean gestational age was 7.56±1.88 weeks and the mean parity was 2.02±0.74 children. Ectopic pregnancy on ultrasound was diagnosed in 159(75.4%) females and on surgery ectopic pregnancy was found in 157(74.4%) females. The sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of abdominal ultrasound for detecting ectopic pregnancy was 97.4%, 89%, 96.3%, 92.3% and 95.2% respectively. Conclusion: Transabdominal ultrasound had a high diagnostic accuracy for detecting ectopic pregnancy.